History, periodization and the character of contemporary crime control - Churchill, David (Criminology & criminal justice, 2019)
In recent decades, several highly influential studies have sought to articulate the changed and changing character of contemporary crime control in its historical context. While the substantive claims of these studies have attracted close scrutiny, there has been remarkably little analysis of the historiographical apparatus underpinning them. As a result, criminology has neglected to develop a valuable, critical vantage point on how crime and justice in our own times are understood. This article advances discussion of contemporary crime control by critically assessing the historiographical foundations of existing studies. Furthermore, it outlines a new approach to analysing the governance of crime through time, which might facilitate a more empirically robust and satisfactory characterization of contemporary crime control. More broadly, the article signals the significance of history and historiography for contemporary criminological scholarship, and reflects upon the advantages of developing a more fully historical criminology.